The Influence of Digital Happiness, Ease of Access, Transaction Security, and Feature Innovation on Digital Loyalty - Muhammad Awaluddin; Gunadi Dwi Hantoro (Research Horizon, 2026)
The rapid development of digital technology has transformed the banking industry, particularly through the emergence of mobile banking services that enable users to conduct financial transactions more efficiently and conveniently. As competition among digital banking platforms intensifies, understanding the factors that influence customer loyalty has become increasingly important. This study aims to examine the influence of digital happiness, ease of access, transaction security, and feature innovation on digital loyalty among mobile banking users. This research employed a quantitative approach using a survey method. Data were collected from 412 mobile banking users through structured questionnaires. The data were analyzed using multiple linear regression analysis to examine the relationships between the independent variables and digital loyalty. The results show that digital happiness, ease of access, transaction security, and feature innovation have positive and significant effects on digital loyalty. These findings suggest that both emotional factors (digital happiness) and functional factors (ease of access, security, and innovation) play important roles in enhancing digital loyalty. Therefore, banking institutions should focus on improving user experience, strengthening transaction security, and continuously developing innovative features to maintain long-term relationships with customers in the digital banking environment.